Trios for violin, viola, and cello, op. 9, ca. 1803 reprint of Pleyel's edition - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Pleyel; Paris; France, 2023)
Three string trios in G major, D major, and C minor, op. 9, published by Pleyel between 1803-1806 from plates of its edition from 1799.